University students' memories of their secondary science education experiences - Aydin, Semih; Kosarenko, Nikolay N.; Khlusyanov, Oleg V.; Malakhovskaya, Vera V.; Kameneva, Galina N. (Frontiers in Education, 2022)
Students' attitudes and perceptions about a course of study and their career choices are influenced by their prior educational experiences. These experiences also apply to physics education, which is not exempt from this process. University students' attitudes toward physics classes during their high school years, the teaching methods used in the course, and their opinions about studying physics are investigated in this study. Students majoring in education, engineering, and health sciences at a university in northern Iraq participated in the survey. The survey collected data from 243 students. The researchers designed a survey that was used to collect data. Descriptive statistics, cluster analysis, and the Mann–Whitney and Kruskal–Wallis tests were used to answer the research questions. The results show that students' opinions about high school physics classes can be positive. Students' attitudes and thoughts do not change according to gender, school status, grade level, or departments. The use of technology and supporting course materials were effective in all dimensions.